Characterization of Volatile Organic Compound Metabolites in Cigarette Smokers, Electronic Nicotine Device Users, Dual Users, and Nonusers of Tobacco. Issue 2 (13th February 2019) - Keith, Rachel J; Fetterman, Jessica L; Orimoloye, Olusola A; Dardari, Zeina; Lorkiewicz, Pawel K; Hamburg, Naomi M; DeFilippis, Andrew P; Blaha, Michael J; Bhatnagar, Aruni
Abstract: Introduction: Limited research exists about the possible cardiovascular effects of electronic nicotine delivery systems (ENDS). We therefore sought to compare exposure to known or potentially cardiotoxic volatile organic compounds (VOCs) in ENDS users, smokers, and dual users. Methods: A total of 371 individuals from the Cardiovascular Injury due to Tobacco Use study, a cross-sectional study of healthy participants aged 21–45 years, were categorized as nonusers of tobacco ( n = 87), sole ENDS users ( n = 17), cigarette smokers ( n = 237), and dual users ( n = 30) based on 30-day self-reported tobacco product use patterns. Participants provided urine samples for VOC and nicotine metabolite measurement. We assessed associations between tobacco product use and VOC metabolite measures using multivariable-adjusted linear regression models. Results: Mean (SD) age of the population was 32 (±6.8) years, 55% men. Mean urinary cotinine level in nonusers of tobacco was 2.6 ng/mg creatinine, whereas cotinine levels were similar across all tobacco product use categories (851.6–910.9 ng/mg creatinine). In multivariable-adjusted models, sole ENDS users had higher levels of metabolites of acrolein, acrylamide, acrylonitrile, and xylene compared with nonusers of tobacco, but lower levels of most VOC metabolites compared with cigarette smokers or dual users. In direct comparison of cigarettes smokers and dual users, we found lower levels of metabolites of styrene and xylene in dual users. Conclusion: Although sole ENDS use may be associated with lower VOC exposure compared to cigarette smoking, further study is required to determine the potential health effects of the higher levels of certain reactive aldehydes, including acrolein, in ENDS users compared with nonusers of tobacco. Implications: ENDS use in conjunction with other tobacco products may not significantly reduce exposure to VOC, but sole use does generally reduce some VOC exposure and warrants more in-depth studies.